2008
DOI: 10.1111/j.1365-2141.2008.07426.x
|View full text |Cite
|
Sign up to set email alerts
|

Valproate synergizes with purine nucleoside analogues to induce apoptosis of B‐chronic lymphocytic leukaemia cells

Abstract: Summary Resistance to chemotherapy and drug toxicity are two major concerns of chronic lymphocytic leukaemia (B‐CLL) treatment by purine nucleoside analogues (PNA, i.e. fludarabine and cladribine). We hypothesized that targeting epigenetic changes might address these issues and evaluated the effect of the histone deacetylase inhibitor valproate (VPA) at a clinically relevant concentration. VPA acted in a highly synergistic/additive manner with fludarabine and cladribine to induce apoptosis of B‐CLL cells. Impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 60 publications
3
39
0
Order By: Relevance
“…These results validated earlier reports on cancer cells, 35 leukemia cells 18 and fresh CLL B cells. [20][21][22] Interestingly, we also observe that VPA induces apoptosis in cells from patients with unfavorable cytogenetic abnormalities such as 6q deletion, 17p deletion or showing a complex karyotype (Supplementary data 6). This indicates that the VPA effect would be independent of cytogenetic features, as well as effective in P53-deficient cells that are chemotherapy resistant and associated with a poor outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results validated earlier reports on cancer cells, 35 leukemia cells 18 and fresh CLL B cells. [20][21][22] Interestingly, we also observe that VPA induces apoptosis in cells from patients with unfavorable cytogenetic abnormalities such as 6q deletion, 17p deletion or showing a complex karyotype (Supplementary data 6). This indicates that the VPA effect would be independent of cytogenetic features, as well as effective in P53-deficient cells that are chemotherapy resistant and associated with a poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The increased apoptosis observed when VPA was associated with various drugs seems to be an additive effect after 24 h: indeed, the sum of VPA-induced and drug-induced cell death is very close to the cell death induced by their association (except for bortezomib, for which a clear synergistic effect is observed). Bouzar et al 22 also observed that VPA acted in an additive/synergistic manner with fludarabine and cladribine to induce apoptosis. In this study, we did not observe a high synergistic effect for fludarabine, probably because of the different experimental conditions used (technique, viability vs apoptosis; time of treatment, 24 vs 48 h; concentration, 7 vs 1 mM).…”
Section: Gene Expression Profile Of Vpa-treated Cll B Cells B Stamatomentioning
confidence: 91%
See 1 more Smart Citation
“…However, there is still controversy on which would be the initiating pathway. It has been reported that valproate-mediated apoptosis in CLL cells involved the extrinsic pathway through caspase 8 activation, 28 which is required for mitochondrial amplification loop through BID cleavage and caspase 9 activation. 29 However, the specific mechanism underlying the activation of the extrinsic apoptotic pathway remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that VPA induces apoptosis at a concentration of 10 mM independent of the disease stage according to the Rai system, ZAP-70 and CD38 expression, IGHV status and cytogenetics, but it depends on LDH serum levels. This indicates that It has already been shown that VPA increases acetylation of histones H3 and H4 [19]. Kawagoe et al [17] demonstrated that in a B-myeloid cell line, VPA activates two different apoptotic pathways -a caspase-dependent pathway causing nuclear apoptotic changes and a caspase-independent pathway [17].…”
Section: Discussionmentioning
confidence: 99%